EL AGLUTINOGENE LEWIS EN LA SANGRE DE LOS MEXICANOS - SALAZAR MALLEN, MARIO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
The blood of 81 adults of the Otomie Indians of Mexico and 199 adults of the mixed population of Mexico City tested with anti-Lea serum showed agglutination in 987% and 1142% with gene frequency of Lea=03142 and 03380, respectively These results are
BOL INST ESTUD MED BIOL
Keywords: AGLUTINOGENE, SANGRE, MEXICANOS; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA